Isolation, Purification, Monosaccharide Composition and Antioxidant Activity of Polysaccharides from Cortex Periplocae - Ruiping ZHANG; Zhaohui REN; Haonan ZHANG; Xiaoping ZHANG; Pengfei LIU; Xiaoli WANG (Shipin gongye ke-ji, 2023)
Objective: In this experiment, polysaccharides from cortex periplocae (CPP) were isolated and purified, and their monosaccharide composition and antioxidant activity were investigated, so as to provide a reference for the development and application of CPP in the food industry. Methods: The crude polysaccharides were obtained by aqueous extraction, alcoholic precipitation and protein removal by Sevag method, and four polysaccharide fractions CPP0, CPP1, CPP2 and CPP3 were separated and purified by DEAE-52 cellulose column. The chemical composition, molecular weight, monosaccharide composition, infrared spectrum and antioxidant activity were analyzed. Results: The sugar contents of these four polysaccharides were 82.20%, 77.13%, 75.23% and 72.85%, respectively, and all of them contained glyoxylate. The relative molecular weights were 685, 477, 411 and 572 kDa, respectively. The four polysaccharides were all heteropolysaccharides composed of mannose, rhamnose, galacturonic acid, glucose, galactose and arabinose in different molar ratios. The infrared spectra showed that four polysaccharides contained β-glycosidic bonds and with furan rings. The antioxidant experiments showed that all four polysaccharides had certain antioxidant properties, and the overall antioxidant capacity was in the following order: CPP0>CPP3>CPP1>CPP2. Conclusion: The four acidic polysaccharides extracted from cortex periplocae have high sugar content, high relative molecular weight, and antioxidant activity, among which CPP0 fraction has the best antioxidant activity.